CGIAR Climate Insights, Issue 1, 21 January 2025 - Rabago, Laura; Mukherji, Aditi (CGIAR System Organization, 2025)
Welcome to Issue #1 of Climate Insights 2025, the CGIAR's fortnightly roundup of the latest publications on climate change impacts and adaptation, mitigation measures, and the physical science from the literature. We’re tracking trending topics in the climate space and linking them to our work for a food secure future with a brief comment on the implications of this new research on our own portfolio of climate research for development.